The Collages of Janet Kigusiuq : A Case Study in Inuit Aesthetics - Mohr, Richard D. (Zenodo, 2024)
Presentation at the Inuit Art Society 2024 Annual Meeting, August 16 & 17 in Traverse City, Michigan, United States. https://inuitartsociety.org/ Richard Mohr on “The Collages of Janet Kigusiuq: A Case Study in Inuit Aesthetics” Mohr’s talk celebrates and analyzes the late-life collages of the Baker Lake artist Janet Kigusiuq (1926-2005), and does so as a vehicle to profile some historically fundamental and still common features of Inuit art. In doing so, the presentation hopes to give a reasoned account of what we intuitively understand as Inuit aesthetics and enable collectors of Inuit art to better understand why we love what we love. The talk also briefly suggests that the Kigusiuq collages pose challenges to Inuit art criticism as it is currently conducted. Richard D. Mohr is Professor Emeritus of Philosophy and of the Classics at the University of Illinois at Urbana-Champaign. He has published on Inuit art in Inuit Art Quarterly, Kolaj (Montreal), Above & Beyond (Canadian North), the Proceedings of the 2019 Inuit Studies Conference (Montreal), The Outsider (Chicago), and has frequently contributed articles to the Smithsonian’s annual Arctic Studies Center Newsletter, including “The Umiaks of Little Diomede”(2020). He explains: “We went to the Arctic for Nature but stayed for Culture.” A recorded session of his talk is published on the Youtube channel of Inuit Art Portal, https://www.youtube.com/@theinuitartportal https://youtu.be/RJdE0YQzpO4